Rebalancing Beban Gardu Distribusi Guna Meminimalkan Susut Teknis ULP Taliwang - Savira Rosa Ghozali; Rahman Arifuddin; Resi Dwi Jayanti Kartika (Elposys: Jurnal Sistem Kelistrikan, 2026)
The quality of electrical power is a crucial factor in supporting community activities and stimulating sustainable economic growth in developing regions. In electric power distribution systems, one of the most frequently encountered technical problems is the high level of technical losses caused by neutral current arising from load imbalance among phases on distribution feeders and transformers. The Brang Rea Feeder is identified as having the highest proportion of unbalanced distribution transformers, reaching 37%. The observed ranges of unbalance percentage, neutral current, and technical losses are 21.06%–66.67%, 3.5 A–117.2 A, and 2.36 W–2651.02 W. In practice, efforts to reduce technical losses are commonly implemented through the installation of additional protection systems, which high investment costs. Therefore, this study focuses on the analysis of neutral current and technical losses on the Brang Rea Feeder through the application of the Distribution Transformer Load Management Method, which is considered a more economical and practical alternative. The operating conditions before and after the implementation of this method are validated using ETAP 19.0.1. The scope of this study is limited to the evaluation of load imbalance, neutral current, and technical losses.After implementation, the unbalance percentage was reduced to 0%–19.05%, producing neutral current and technical loss ranges of 0 A–81.10 A and 0 W–1269.36 W. This improvement resulted 32,233.41 kWh energy saved and an additional revenue of IDR 46,567,609.92. Consequently, the contribution of technical losses to total distribution losses without E-Min at PT PLN (Persero) ULP Taliwang was significantly reduced.